Analisis Modal Kerja terhadap Siklus Operasional Perusahaan Studi Kasus Pada PDAM Tirta Pakuan Kota Bogor - Muktiadji, Nusa; Halida, Halida (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2007)
The purpose of this research is to find out gross working capital and net working capital, and how fast operational cycle of a firm. After to be analyzed, it can be established a policy to meet working capital need. The result of this research shows that PDAM Tirta Pakuan Kota Bogor has negative net working capital and has good enough gross working capital (there is an increase every year). The best gross working capital is in 2005. The firm operational cycle has an increase every year, and more and more faster every year. Evaluation result of this research shows that net working capital and speeding up of operational cycle is not able to compensate for overdue long-run debt. Keywords: Working capital analysis; Finance management.